Myoglobin Dynamics Measured With Vibrational Echo Experiments. Issue 1 (1999) - Rector, K. D.; Fayer, M. D.
Abstract : Ps infrared vibrational echo experiments on myoglobin and myoglobin mutants are presented. The vibrational dephasing experiments examine the influence of protein dynamics on the CO ligand, at the active site of myoglobin, from low temperature to physiologically relevant temperatures. The vibrational echo results are combined with measurements of the CO vibrational lifetime to yield the homogeneous pure dephasing. The pure dephasing is the Fourier transform of the homogeneous linewidth with the lifetime contribution removed. The mutant H64V protein's CO vibrational pure dephasing rate is ∼20% slower (narrower pure dephasing linewidth) than the native protein at all temperatures, although the only difference between the two proteins is the replacement of the native's polar distal histidine by a non-polar valine. The mutant H93G(N-MeIm) pure dephasing is identical to the native's, despite the severing of the only covalent bond between the heme and the globin. These results provide insights into the mechanisms of the transmission of protein fluctuations to the CO ligand bound at the active site.